A Hybrid SOAR-BSC-AHP Framework for Strategy Selection in Digital Cultural Tourism - Kurniawan, Rahadian; Kusumadewi, Sri; Sujarwo, Ari (Informatika, Universitas Jenderal Soedirman, 2025)
Digital transformation in cultural tourism presents significant challenges, particularly in heritage villages like Kotagede, Yogyakarta. Problems such as limited infrastructure, low digital literacy, and the absence of a structured planning framework hinder progress toward community-based sustainable tourism development. This study addresses these challenges by proposing an integrated decision-making framework that combines SOAR analysis, the Balanced Scorecard (BSC), and the Analytic Hierarchy Process (AHP). The SOAR-BSC framework captures strategic objectives from qualitative data through focus group discussions and stakeholder interviews, while the AHP quantitatively prioritizes eight strategic alternatives based on hierarchical criteria and subcriteria. The most impactful strategies identified were: (1) developing partnerships with tour operators, and (2) promoting community cultural education and training. The Learning and Growth Perspective emerged as the most influential factor (weight = 0.5549), highlighting the importance of community empowerment and digital skills development. Sensitivity analysis and cross-validation using the Simple Additive Weighting (SAW) method confirmed the consistency and robustness of the rankings. In practice, this framework offers a participatory, data-driven guide for digital transformation in heritage tourism, supporting not only improved destination management but also long-term cultural preservation through inclusive digital initiatives.